SƠ BỘ PHÂN TÍCH TÁC ĐỘNG CỦA BIẾN ĐỔI KHÍ HẬU ĐẾN ĐA DẠNG SINH HỌC VÀ HỆ SINH THÁI CỬA SÔNG HỒNG - Yên, Mai Đình (Nhà xuất bản Nông nghiệp, 2016)
IPCC (Intergovernment Panel of Climate Change) and MONRE (Ministry of Natural Resources and Environment) of Vietnam have delivered different scenarios for some main climatic factors of the Delta of North Vietnam, such as temperature, sea level rise, precipitation for 2020, 2050 and 2100. The biodiversity/ecosystem of the Red River mouth has many characteristics of the history of formation, the living environment, and biodiversity of different groups of aquatic organisms, which have scientific, economic and social values. However, the biodiversity/ecosystem of the Red River mouth is being heavily degraded due to many reasons, of which the most important one is due to construction of many damps in the watershed. For the worst scenario, the impacts of climate change on biodiversity/ecosystem of the Red River mouth are very severe because they will affect the species composition of the different groups of aquatic organisms and their living environment. These impacts will be accelerated, since biodiversity/ecosystem has presently been heavily degraded. It is necessary to prepare and implement systematically measures to mitigate negative impacts on biodiversity/ecosystem and to adapt better to climate change.